Effects of different granular viscosity models on the bubbling fluidized bed - A numerical approach - Hilmee, M.I. (2013)
Kinetic Theory of Granular Flow (KTGF) has been successfully incorporated and widely implemented in the Eulerian simulation models in many multiphase cases. The KTGF theory involves many parameters and is applied in the multiphase simulation for the purpose of hydrodynamic properties modeling of the granular phase. This paper is focused on granular viscosity which is a parameter in the KTGF that incorporates three different viscosities arising from the inter-phase and intra phases' interaction in a bubbling fluidized bed (BFB). The 2D BFB model of 0.2 m width and 0.8 m length having a 13-hole orifice plate has been modeled for this purpose. The model was constructed using Gambit software version 2.4.6 and then simulated using ANSYS Fluent version 14. Two models of granular viscosity, namely Syamlal-Obrien model and Gidaspow model, were compared based on its effect to the pressure drop and bed expansion of the BFB. The results depicted that the simulation based on Syamlal-Obrien model tends to produce larger bubbles and contributing to a higher pressure drop across the distributor plate as compared to the Gidaspow model. Â© (2013) Trans Tech Publications, Switzerland.